Evaluating Financial Condition of Local Governments in Indonesia: Benchmarking and Determinant Factors - Nugroho, Enggar Hestu (2020)
This study examines the second-tier of Indonesia’s subnational authorities’ financial conditions. Based on financial condition composite index (FCCI) of Ritonga et al. (2012), Local Governments (LGs) are measured using their financial statements by selected financial ratios. FCCI method is performed to obtain each LG index. Subsequently, those LGs are compared and ranked with Zafra-Gómez (2009b) benchmarking method. Finally, it aims to test the hypothesis of factors affecting FCCI proposed by Ritonga et al. (2019). This research analyses LG in Indonesia for the period 2015-2018. It observes 508 LGs, consisted of 415 regencies and 94 cities governments. It utilises cluster analysis and multiple regression analysis. Clustering variables are based on selected socioeconomic and demographics indicators utilised by the central government for allocating general intergovernmental funds to LGs. After analysing those indicators, cluster analysis reports five clusters of regencies and six clusters of cities. The study finds that the financial efficiency of LG and gross regional domestic product per capita have a positive association with financial conditions for regencies and cities. Population size growth more likely deteriorates regencies' financial health, while population density has a positive relation to regencies. However, both variables do not have a significant influence on financial condition of city governments. It also reveals that the wealth of community has a contradicting result in regencies and cities. Meanwhile, it is confirmed that the age profile of community and cost of services and goods do not affect financial condition at all types of organisations.